Peningkatan Kualitas Pembelajaran Pengolahan Citra Digital Pada Program Studi Teknik Informatika Menggunakan Model Problem Based Learning - Mila Nurjanah; Yovi Litanianda (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
This research explores the application of the Problem-Based Learning (PBL) model to improve the quality of digital image processing learning in the Informatics Engineering Study Program. Through in-depth interviews, observations, and document analysis, this research shows that PBL has a positive impact on students' conceptual understanding, technical skills, and involvement in the learning process. Nevertheless, challenges such as planning relevant learning problems and evaluating the learning process were also identified. Support and training are needed for lecturers to overcome these challenges. These findings provide valuable insights for the development of problem-based teaching practices in the context of digital image processing.